Zooplankton Diversity and Ecological Variations of Coastal Wetlands of Bakerganj, Bangladesh (Bangladesh Journal of Zoology, 2023)
Ecology and diversity of zooplankton species in relation to some physico-chemical parameters at three sites namely Thana Health Complex Pond, Tulatoli River and Harun Dakua’s Pond of the coastal ecosystems of Bakerganj were studied from January 2008 to December 2009. A total of 56 zooplankton species were recorded out of which 35 were rotifers, 6 protozoan, 8 copepods, 5 cladocerans and 2 ostracods species. During study, rotifera was the most abundant group (61.44 % in Thana Health Complex pond, 38.36 % in Tulatoli River, and 86.03 % in Harun Dakua’s pond), while the ostracoda were the least abundant group (0.2 % in Harun Dakua’s pond). The highest monthly average value of zooplankton was 707.75 ± 189.56 indv /L at Thana Health Complex pond and the lowest was 127.42 ± 19.95 indv /L at Tulatoli River of Bakerganj. Zooplankton species richness (R1 and R2) was comparatively higher (R1: 1.63 ± 0.10; R2: 0.64 ± 0.06) in Harun Dakua’s pond while both the species diversity (Shanon Weiner Index) (H' = 0.87 ± 0.08; eH' = 2.52 ± 0.17) and species evenness (E1 and E2) (E1 = 0.44 ± 0.04; E2 = 0.43 ± 0.05) were higher in the Tulatoli River. The zooplankton population showed positive correlation with physico-chemical parameters like water temperature, air temperature and water depth, whereas negatively correlated with pH, DO, TDS, conductivity and salinity with a few exception.Bangladesh J. Zool. 50(3): 321-335, 2022